Evaluasi Implementasi SIMDA Keuangan Menggunakan TAM pada Dinas Kependudukan dan Pencatatan Sipil Provinsi Sumatera Utara - Rafisa, Ayu Widyastuti; Aisyah, Siti (ARZUSIN, 2022)
This study's objective was to investigate and evaluate how the Technology Acceptance Model (TAM) affected the accuracy of data on the accrual-based Financial Regional Management Information System (SIMDA) at the North Sumatra Province's Department of Population and Civil Registration. The Department of Population and Civil Registration in North Sumatra Province used a survey to gather data for this study, which included information collected directly from respondents, observation, and the use of a questionnaire delivered to three operators utilizing SIMDA Finance. With a total of 3 respondents, the respondents were workers who used the SIMDA Finance application. The outcomes demonstrated that the accrual-based SIMDA Finance implementation went very well, and the study's respondents stated that all work could be accomplished correctly.